Myths of State Officials and People’s in Indonesian Political Meme on Instagram (Roland Barthes Semiotics Review) - Munawarah Munawarah; Mayong Mayong; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2021)
Abstract. This study aims to identify myths in Indonesian political memes. The data in the study were processed by means of data reduction, data presentation, conclusion drawing and verification. The object of this research is memes that contain politics and myths that exist in these political memes. Memes are one of the media to express opinions in a different way than usual, namely with pictures and writing. One of them is in the political field, memes become a tool for campaigning and the media for conveying criticism and suggestions. With Roland Barthes' semiotic theory, researchers will reveal the denotations, connotations and myths contained in Indonesian political memes. Therefore, this research focuses on problem formulations, namely How is the myth according to Roland Barthes in Indonesian political memes? The results of the analysis show that First, there are various myths in Indonesian political memes. one of which is about if we want to be rich we must become politicians/officials, that work as a politician/official is not the only way and way to achieve success. Keywords: Meme, Myth, Roland Barthes Semiotics, and Instagram